Origin of the monolayer Raman signature in hexagonal boron nitride: a first-principles analysis. (12th April 2018) - Ontaneda, Jorge; Singh, Anjali; Waghmare, Umesh V; Grau-Crespo, Ricardo
Abstract: Monolayers of hexagonal boron nitride ( h -BN) can in principle be identified by a Raman signature, consisting of an upshift in the frequency of the E2g vibrational mode with respect to the bulk value, but the origin of this shift (intrinsic or support-induced) is still debated. Herein we use density functional theory calculations to investigate whether there is an intrinsic Raman shift in the h -BN monolayer in comparison with the bulk. There is universal agreement among all tested functionals in predicting the magnitude of the frequency shift upon a variation in the in-plane cell parameter. It is clear that a small in-plane contraction can explain the Raman peak upshift from bulk to monolayer. However, we show that the larger in-plane parameter in the bulk (compared to the monolayer) results from non-local correlation effects, which cannot be accounted for by local functionals or those with empirical dispersion corrections. Using a non-local-correlation functional, we then investigate the effect of finite temperatures on the Raman signature. We demonstrate that bulk h -BN thermally expands in the direction perpendicular to the layers, while the intralayer distances slightly contract, in agreement with observed experimental behavior. Interestingly, the difference in in-plane cell parameter between bulk and monolayer decreases with temperature, and becomes very small at room temperature. We conclude that the different thermal expansion of bulk and monolayer partially 'erases' the intrinsic Raman signature, accounting for its small magnitude in recent experiments on suspended samples.